Institutional Capacity of Innovation Activity Development in theRegion - Aleksei Aleksandrovich Rumyantsev (Economic and Social Changes: Facts, Trends, Forecast, 2016)
The article presents the results of the study under the theme of development of institutions of innovation sphere, transfer of scientific results to the real sector of the economy. The purpose of the study is to reveal institutional capacities of strengthening the implementation of research findings, drawing on the functional properties of institutions with regard to innovation activities. The methodology is to apply well-known methodological principles to the solution of emerging challenges (software-based method for fundamental scientific result implementation, sectoral research organizations in the new management environment and statistical records of process innovations by analogy with product innovations). The article puts forward and justifies the proposal for strategic innovation as the institution of communicating the results of fundamental research to social practice by integrating into a single process the results of oriented fundamental research, applied research, engineering development, development and other works, which are realized in the form of a material object or service of a high technology level. The distinguishing feature of strategic innovation is a future-oriented outlook and the solution of long-term objectives. Russian scientific achievements can become the basis for strategic innovation development. The article gives examples of possible research field where strategic innovation can be developed and demonstrates an innovative implementation mechanism in the format of specialized research-and-production program which combines government and business participation. The paper gives arguments and development ways of the institution of sectoral research organizations as providers of state technological policy in sectors and regions; coordination of import substitution; centers of communication establishment with engineering companies; analytical and predictive research. The study justifies the expediency of developing an institution for statistical innovation records by introducing the indicator of weight of innovative production technologies which are of particular importance to the measurement and management of innovation processes in extractive industries and regions. We have worked out a proposal for the development of the institution of scientific and technical programming by making an annual operational program implementation plan. The results of the study can be applied to fundamental research results programming and may also be used by federal and regional authorities in the system of measures for the development of national and regional innovation systems. The study can be pursued in line with the proposed institutions in terms of clarifying state financing and the provision of a preference for businesses units within strategic innovation, the introduction of pilot projects on the measurement of process innovation, the development of a short-term scientific and technical program implementation plan